In Vitro Cytotoxicity of GuttaFlow Bioseal, GuttaFlow 2, AH-Plus and MTA Fillapex - Saygili, Gokhan; Saygili, Suna; Tuglu, Ibrahim; Capar, Ismail Davut (Iranian Endodontic Journal, 2017)
Introduction: The aim of the present in vitro study was to evaluate the cytotoxicity of different sealers including GuttaFlow Bioseal, GuttaFlow 2, AH-Plus and MTA Fillapex on L929 murine fibroblasts. Methods and Materials: Samples of GuttaFlow Bioseal, GuttaFlow 2, AH-Plus and MTA Fillapex were fabricated in Teflon disks of 5 mm diameter and 3 mm thickness. L929 fibroblasts were exposed to the extracts of these materials for 3, 24, 72 and 168 h at 37°C with 5% CO2. Cell viability was evaluated by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was evaluated by the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assay. The data were analysed by ANOVA. Results: GuttaFlow Bioseal was nontoxic at all experimental time points (P>0.05), whereas MTA Fillapex and AH-Plus were toxic (P<0.001). At 7 days, there were more viable cells in the GuttaFlow 2 group than in the control group, and MTA Fillapex was more cytotoxic than AH-Plus. There were more apoptotic cells in the MTA Fillapex and AH-Plus groups than in the other groups at 3 h (P<0.001). Conclusion: GuttaFlow sealers are less cytotoxic than MTA Fillapex and AH-Plus. At all experimental time points, there was no significant difference in the cell viability between the GuttaFlow Bioseal group and the control group. Keywords: AH-Plus; Cytotoxicity; GuttaFlow Bioseal; GuttaFlow 2; MTA Fillapex; MTT Assay; TUNEL Assay